Rare hereditary red blood cell enzymopathies associated with hemolytic anemia – pathophysiology, clinical aspects, and laboratory diagnosis. (June 2014) - Koralkova, P.; van, W. W.; van, R.
Summary Hereditary red blood cell enzymopathies are genetic disorders affecting genes encoding red blood cell enzymes. They cause a specific type of anemia designated hereditary nonspherocytic hemolytic anemia (HNSHA). Enzymopathies affect cellular metabolism, which, in the red cell, mainly consists of anaerobic glycolysis, the hexose monophosphate shunt, glutathione metabolism, and nucleotide metabolism. Enzymopathies are commonly associated with normocytic normochromic hemolytic anemia. In contrast to other hereditary red cell disorders such as membrane disorders or hemoglobinopathies, the morphology of the red blood cell shows no specific abnormalities. Diagnosis is based on detection of reduced specific enzyme activity and molecular characterization of the defect on the DNA level. The most common enzyme disorders are deficiencies of glucose‐6‐phosphate dehydrogenase (G6PD) and pyruvate kinase (PK). However, there are a number of other enzyme disorders, often much less known, causing HNSHA. These disorders are rare and often underdiagnosed, and the purpose of this review. In this brief review, we provide an overview of clinically relevant enzymes, their function in red cell metabolism, and key aspects of laboratory diagnosis.